Crash analysis of racing car nose cone subjected to full frontal impact - Abdul Aziz, Nuraini; Zulkifli, Norzima; A. Hamid, Amar Ridzuan (Penerbit UTM Press, 2015)
Racing a car involves high-speed and having high possibility to crash either among the racer or hitting the bench. Concerning the driver safety, impact structures such as nose cone is designed to absorb the race car kinetic energy to limit the decelerations acting on the human body. In this study, analysis of different type of nose cone material were conducted. The objective is to find the highest specific energy absorption (SEA) based on three different materials which are mild steel, aluminium and composite material. The nose cone was modelled using CATIA V5R16 while the crash simulation was done using LS-DYNA and LS-Prepost software with an average velocity of 80km/hour according to United States New Car Assessment Program (US-NCAP) frontal impact velocity and based on European Enhanced Vehicle-safety Committee. The simulation results show that fiberglass E with thickness of 2.6 mm and lay-up configurations of [0°/30°/60°/90°/120°] give the highest internal energy and specific energy absorption of 41.28845 kJ and 6.9104 kJ/kg. This concludes that fiberglass E is a suitable material to build a lightweight structure compared to steel and aluminium.